Última Hora: uma tribuna do governo e dos trabalhadores - Padovani, Patrícia Ribeiro dos Reis (2016)
This research deals with the intersection between the interests of the government and the interests of the working class in the pages of the Last Hour. Created to defend and spread the Getulio Vargas policy and respond to criticism of other media outlets, the newspaper also had as main objective to represent the interests of ordinary people, especially the workers. The chronological cut for this analysis was the second government of Vargas, located 1950-1954 and timeframe of this study is 1951 appearance of the year of the Last Hour. The paper identifies how the labor movement has been portrayed in this paper, through the analysis of news coverage in key moments of representation of political ideology during the second government of Vargas: the celebrations by then the president’s birthday and Labor Day and João Goulart management in front of the Ministry of Labor, Industry and Commerce. The research also analyzes the coverage of two major strikes that happened in the period: the strike of 300,000 and Greve Mariners, both in 1953 and the spaces reserved for the claims of the workers in the pages of newspapers: the column 'Tell the people in UH 'and the realization of simulated popular courts against the economy of the people.